Лучшее в тебе - Глайнс Эбби (Young Adult, 2020)
На обложке: Автор бестселлеров USA Today Экземпляры: ЦБ (20211220) / Инвентарный номер: 54763 / Цена: 313.00 / Сис.шифр: 84(4/8) / Авт.знак: Г 52 / ГРНТИ: 17.82 / ББК: 84(7Сое)-44